Scientific Pedagogical Issues Of Applying Informational Technologies In The Education System - Kamoliddin Rakhmatullaevich Mamadaliyev (Euro Asian Journal Publishing, 2024)
This article discusses the scientific pedagogical issues of applying informational technologies, the practice of using computer telecommunication in the education system, and the use of information technologies in the educational process. It emphasizes not only watching and acquiring information from the screen but also involving students creatively in this process.
Keywords: educational process; pedagogical technologies; informational culture